2018
DOI: 10.1038/s41598-018-34801-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irrigation conditions in the germination of plasma treated Nasturtium seeds

Abstract: Plasma treatments had emerged as a useful technique to improve seed germination. In this work we investigate the influence of different irrigation conditions and plasma treatments on the germination of nasturtium seeds. During plasma treatment, seeds experience a progressive weight loss as a function of treatment time that has been associated to water release, a process that is more pronounced after longer plasma treatment times. Seeds treated for short times (<30 s) are able to germinate more efficiently than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 50 publications
4
58
0
Order By: Relevance
“…Moreover, they showed that the enlarged water absorption, compared to the initial seed, was directly related to a better seed germination. The similar germination tendencies were observed by other authors as well, when the plasma treatment encouraged the seeds surface hydrophilicity, which is directly related to a better germination process [10,43,44]. The water contact angle measurement is a simple technique which is used for a qualitative evaluation of surface wettability.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, they showed that the enlarged water absorption, compared to the initial seed, was directly related to a better seed germination. The similar germination tendencies were observed by other authors as well, when the plasma treatment encouraged the seeds surface hydrophilicity, which is directly related to a better germination process [10,43,44]. The water contact angle measurement is a simple technique which is used for a qualitative evaluation of surface wettability.…”
Section: Resultssupporting
confidence: 77%
“…This means that only a very top layer of the seeds surface is altered during the plasma treatment and such a method does not make any changes on the seeds bulk. However, a majority of the researchers claimed that the plasma ion penetration depth into the various seeds is up to 10 nm [10,32,33]. This disparity between the calculated results and the ion penetration depth provided by other authors could be related to several approaches.…”
Section: Simulation Resultsmentioning
confidence: 82%
“…Therefore, it is suggested that the previously observed more asymptomatic weight loss could be related to incomplete removal of the pericarp outer layer and to the cessation of water release after a certain plasma treatment time. [ 7 ] When taking a look at the SEM images of the cross‐sectioned seeds, one can clearly discern the noteworthy surface character of the etching processes, as evidenced by the similar microstructure of the inner part of seeds before and after plasma treatment (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…In line with the ample evidence in literature about the positive effect of plasma treatments in improving seed germination, a similar effect can be noticed in this study for wheat seeds, with extra findings showing that (a) water scarcity (dry and medium environments) that drastically conditions the germination can be compensated by short plasma treatments, whereas (b) water abundance significantly accelerates the germination that becomes less affected by plasma treatment. [ 7 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation